Investigation On the Effect of Supercritical CO2 Treatment On Shale Properties: Implications for CO2 Sequestration - Ahmed Mohammed, Ahmed Fatah Alrahman (Curtin University, 2022)
This thesis evaluates the reactivity of different types of shales to SCCO2 treatment during CO2 storage. The relationship between shale mineralogy and pore structure was defined, and new insights on the wettability behavior were provided. The reactive-transport kinetic model indicated significant dissolutions of carbonate and clay minerals, which can enhance the trapping mechanism through mineralization process. The overall results of this project confirmed the high storage capacity and seal integrity of shales to store CO2.